ADVANCES IN SURGICAL RESECTION TECHNIQUES FOR GLIOBLASTOMA: IMPLICATIONS FOR SURVIVAL AND PRECISION. A REVIEW OF CURRENT LITERATURE - Wiktoria Suchcicka; Aleksandra Borowy; Aleksandra Chajnowska; Julia Guzowska; Patrycja Rzeźnik; Maciej Sobczyk; Weronika Stachera; Julia Stępień; Barbara Wołoszyn; Małgorzata Zach (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Glioblastoma multiforme is the most common and aggressive type of primary brain tumor, often presenting with a poor prognosis and limited survival, despite available treatment options. The tumor’s inherent resistance to treatment and its heterogeneity pose significant challenges for management. Aim: This article aims to assess the impact of various surgical resection techniques on the survival of patients with glioblastoma, focusing on the importance of maximizing tumor resection while minimizing postoperative complications. Methods and Materials: A literature review was conducted, focusing on studies published in the past five years. The review examined factors such as the extent of surgical resection, the use of intraoperative guidance, and postoperative care, evaluating their influence on survival rates. Discussion: Complete tumor resection is positively associated with improved survival, but the extent of resection remains a debated topic. Advanced surgical methods, including fluorescence-guided imaging, are increasingly used to improve resection accuracy and reduce harm to healthy tissue. However, the prognosis for glioblastoma patients remains poor, and new approaches are needed to address the tumor’s resistance mechanisms. Conclusions: Surgical resection is a key component of glioblastoma treatment, with a significant impact on survival. However, there is a need for further clinical studies to refine surgical methods, optimize resection strategies, and develop new therapeutic options to improve long-term survival for patients.